2019
DOI: 10.3390/ijerph16061031
|View full text |Cite
|
Sign up to set email alerts
|

Health Assessment of Trace Metal Concentrations in Organic Fertilizer in Northern China

Abstract: The application of organic fertilizer could be accompanied by potential hazards to soil and humans caused by trace metals. A wide survey of organic fertilizers was carried out in northern China. A total of 117 organic fertilizer samples were collected to analyze the concentrations of seven trace metals. Simulation models were used to estimate the trace metal accumulation risk in soil and non-carcinogenic and carcinogenic risks to the human body. The concentrations of trace metals varied widely (Cr: 2.74–151.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 51 publications
1
20
0
4
Order By: Relevance
“…Chibueze, et al [24] evaluated the heavy metals concentrations in farmyard manure and chemical fertilizers used in Southeastern Nigeria, a high prevalence of Iron (Fe) concentration in pig manure was observed as compared with synthetic fertilizers. Similarly, Gong, et al [20] assessed the concentrations of trace metals in 117 animal-based manures; it was observed that the concentrations of Chromium (Cr), Cadmium (Cd), Lead (Pb), and Arsenic (As) all exceeded the Chinese organic fertilizers standards limits in the range of 0.85 -5.98% while the concentrations of Nickel (Ni), Copper (Cu) and Zinc (Zn) exceeded the limits set by the German authority in the range of 1.17 -35.04%.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Chibueze, et al [24] evaluated the heavy metals concentrations in farmyard manure and chemical fertilizers used in Southeastern Nigeria, a high prevalence of Iron (Fe) concentration in pig manure was observed as compared with synthetic fertilizers. Similarly, Gong, et al [20] assessed the concentrations of trace metals in 117 animal-based manures; it was observed that the concentrations of Chromium (Cr), Cadmium (Cd), Lead (Pb), and Arsenic (As) all exceeded the Chinese organic fertilizers standards limits in the range of 0.85 -5.98% while the concentrations of Nickel (Ni), Copper (Cu) and Zinc (Zn) exceeded the limits set by the German authority in the range of 1.17 -35.04%.…”
Section: Introductionmentioning
confidence: 90%
“…The numerous benefits and the suitability of MP-AES for metal analysis have been rigorously reviewed by Balaram [35]. According to Gong, et al [20] the chemical analysis of standard samples, duplicate samples, and method blanks was equally carried out to ensure quality control and assurance. Prior to chemical analysis, 1 gram (dry weight) of each sample, in admixture with 4 ml of 50% nitric acid (HNO3) and 10ml of 20% Hydrochloric acid (HCl), was prepared.…”
Section: Analysis Of Samples For Heavy Metal Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying quality-controlled organic residues from industry on agricultural land may contribute to an extensive circular economy. Reducing mineral P fertilizers may also help decrease the input of harmful trace elements such as cadmium or uranium [47]; the application of secondary raw material fertilizers should be monitored by quality control measures [48,49]. In the past, intensive farming with excessive N and P fertilization have caused nutrient losses to surface and subsurface water, generating environmental harm in the form of nitrate leaching and eutrophication [50,51].…”
Section: Food Securitymentioning
confidence: 99%
“…In addition, the disposal of waste and the application of pesticides and fertilizers can increase the concentration of potentially toxic elements (PTEs), such as Pb, Cd, Cu, Mn, Zn and Hg, in soils and groundwater, which may cause toxicity risks to the ecosystem and human health [11][12][13][14][15][16][17]. Although these elements occur naturally, anthropogenic sources contribute significantly to increased rates of PTE redistribution among the compartments of the environment [18,19].…”
Section: Introductionmentioning
confidence: 99%